THE SULFONATION STUDY OF REACTION MECHANISM ON PAPAVERINE ALKALOID BY GC-MS AND FT-IR - I Made Sudarma (Universitas Gadjah Mada, 2007)
The aim of this research was to prove theoretical mechanism reaction on the sulfonation of papaverine alkaloid and the result could be used as a reference on the transformation of these alkaloid to the other derivatives. Theoriticaly sulfonation of papaverine (1) by HO-SO2Cl could produced papaverine sulfonyl chloride (1a). The formation of this product was analyzed by analytical thin layer chromatography GC-MS, and FT-IR. These analysis showed the formation of product (1a) more favorable than the other. Tlc showed product (1a) less polar than papaverine, and supported by GC-MS and infrared which showed molecular ion at m/z 412 due to the presence of -SO2Cl and vibration at 1153,4 dan 1265,2 Cm-1 due to absorption of sulfonyl group.